2017
DOI: 10.4239/wjd.v8.i7.346
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in subjects with or without chronic kidney disease among Veterans with diabetes in North East United States

Abstract: AIMTo evaluate the prevalence of vitamin D deficiency and its relation to diabetes and kidney disease in Veterans residing in the North East United States (VISN 2).METHODSIn this retrospective study, we used data from the computerized patient record system at Stratton Veterans Administration Medical Center at Albany, NY (VHA) for those patients who had 25-hydroxyvitamin D levels and 1,25 (OH) vitamin D levels measured between 2007 and 2010. We collected demographic information including age, sex, body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, in a retrospective study executed by Sipahi et al that registered 1463 patients with type 2 diabetes mellitus and chronic kidney disease, 52.0% of the subjects had vitamin D deficiency and 24.0% presented with vitamin insufficiency [ 73 ]. However, a study by Yaturus et al showed insufficient levels of vitamin D levels in both diabetic and non-diabetic patients with chronic renal failure and no-significant difference between the two groups [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a retrospective study executed by Sipahi et al that registered 1463 patients with type 2 diabetes mellitus and chronic kidney disease, 52.0% of the subjects had vitamin D deficiency and 24.0% presented with vitamin insufficiency [ 73 ]. However, a study by Yaturus et al showed insufficient levels of vitamin D levels in both diabetic and non-diabetic patients with chronic renal failure and no-significant difference between the two groups [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…35 The prevalence of 25(OH)D deficiency is common in CKD and is implicated in the progressive increase in PTH, which is observed with declining renal function and leads to secondary hyperparathyroidism, bone mineral disease and increased cardiovascular risk. 41 In the study, no correlation between PTH and 25(OH)D was observed. This result is similar to that observed by Cuppari et al, 42 in a cohort that involved 144 patients with CKD who did not yet receive dialysis (CKD stages 2 to 5), demonstrated that the 25 (OH) D levels were not associated with PTH.…”
mentioning
confidence: 64%
“…When analyzing eGFR, some studies described a direct interaction between 25(OH)D and GFR, 15 , 16 whereas other authors did not confirm this finding. 7 , 8 , 12 , 15 , 18 , 27 As we and others have previously demonstrated, the accuracy of GFR estimated by equations is poor, especially in patients with diabetes, markedly underestimating true GFR. 21 , 28 30 This finding is probably due to either analytical factors, such as interference of glucose levels on creatinine measurement, or to the lack of sensitivity of creatinine to identify glomerular hyperfiltration, a peculiar scenario in diabetes.…”
Section: Discussionmentioning
confidence: 99%